The Role of Artistic Creative Activities in Navigating the COVID-19 Pandemic in Australia - Kiernan, Frederic; Chmiel, Anthony; Garrido, Sandra; Hickey, Martha; Davidson, Jane W. (Frontiers in Psychology, 2021)
During the COVID-19 pandemic some Australians turned to artistic creative activities (ACAs) as a way of managing their own mental health and wellbeing. This study examined the role of ACAs in regulating emotion and supporting mental health and wellbeing during the COVID-19 pandemic, and also attempted to identify at-risk populations. We proposed that 1) participants would use ACAs as avoidance-based emotion regulation strategies; and 2) music engagement would be used for emotion regulation. Australian participants (N = 653) recruited from the general public completed an online survey, which included scales targeting anxiety (GAD7 scale), depression (PHQ9 scale) and loneliness (two UCLA Loneliness Scales, referring to “Before” and “Since” COVID-19). Participants reported which ACAs they had undertaken and ceased during the pandemic using an established list and ranked their undertaken ACAs in terms of effectiveness at making them “feel better”. For their top-ranked ACA, participants then completed the Emotion Regulation Scale for Artistic Creative Activities (ERS-ACA), and if participants had undertaken any musical ACAs, also the Musical Engagement Questionnaire (MusEQ). The results supported both hypotheses. ANOVAs indicated that participants ranked significantly higher on the “avoidance” ERS-ACA subscale than the other subscales, and that participants ranked significantly higher on the emotion regulation and musical preference MusEQ subscales than the other subscales. Additionally, while ACAs such as “Watching films or TV shows” and “Cookery or baking” were common, they ranked poorly as effective methods of emotion regulation, whereas “Listening to music” was the second-most frequently undertaken ACA and also the most effective. “Singing” and “Dancing” were among the most ceased ACAs but also ranked among the most effective for emotion regulation, suggesting that support for developing pandemic-safe approaches to these ACAs may provide wellbeing benefits in future crises. Additionally, correlation analyses showed that younger participants, those who took less exercise during the pandemic, and those with the highest musical engagement reported the poorest wellbeing. We conclude that ACAs provided an important resource for supporting mental health and wellbeing during the COVID-19 pandemic in Australia and could potentially support mental health and wellbeing in future crises.